Monascus-fermented monascin and ankaflavin improve the memory and learning ability in amyloid β-protein intracerebroventricular-infused rat via the suppression of Alzheimer's disease risk factors. (October 2015) - Lee, Chun-Lin; Lin, Pei-Ying; Hsu, Ya-Wen; Pan, Tzu-Ming
Highlights: Monascus purpureus -produced Monascin (MS) and ankaflavin (AK) prevented AD development in Aβ40-induced AD rats. Feeding MS and AK to Aβ40-induced AD rats improved their performance in the reference memory tests and working memory tests. MS and AK reduced the protein levels of p -tau, apo E and BACE in the hippocampi and cortex. The accumulation of Aβ40 was decreased, and the expression of sAPPα, a protection factor of nerve cells, was increased. Abstract: Amyloid-β peptide (Aβ) deposition in the brain damages neurons and eventually results in Alzheimer's disease (AD), and which can be aggravated by cholesterol and high-fat diets. Monascus purpureus -fermented product was proven to prevent AD development. However, the functional compound and mechanism are still unclear. Monascin (MS) and ankaflavin (AK) produced by M. purpureus exhibit antiinflammatory, antioxidative, and hypolipidaemic effects. In this study, serious AD model rats induced by high fat diet and continuous intracerebroventricular (icv) infusion with Aβ40 for 28 days were used to investigate the alleviating and prophylactic effects of MS and AK on the memory and learning abilities, as well as the AD risk factor levels. The results show that feeding MS and AK to AD-induced rats improved their performance ( p   <  0.05) in both the reference memory and working memory tests. Finally, MS and AK reduced the protein levels of p -tau, apolipoprotein E (apo E) and beta-site amyloid precursor protein-cleaving enzyme (BACE) in the hippocampi and cortex. Moreover, the accumulation of Aβ40 was decreased, and the expression of soluble amyloid precursor protein α (sAPPα), which serves as a protection factor of nerve cells, was increased. Therefore, MS and AK can improve the memory and learning ability in Aβ40 icv infused rat via the suppression of AD risk factors.